Daily intake of a homeopathic agent by dogs modulates white cell defenses and reduces bacterial counts in feces - Jaguezeski A.M. (2021)
© 2021 Elsevier LtdMotivated by conventional medicines' ineffectiveness and the appearance of bacterial resistance, homeopathic medicines are being increasingly demanded by the veterinary market. Dog feces contain high bacterial and pathogenic loads, which can cause diseases in animals and facilitate zoonotic transmission. Adequate animal immunity contributes to the elimination of potential pathogens. This work's objective was to evaluate the effects of using a homeopathic medication on blood cell counts, serum protein levels, and fecal bacterial counts in dogs. Two groups were used, each including five 19-month-old Beagle dogs. The homeopathic product Orgainfecto® was sprayed on the two daily meals in the treated group (T), at 0.5 mL/animal/day for 60 days; the group that did not receive the homeopathic was considered the control (C), who were fed only the vehicle used in the production of the homeopathic as a placebo. On days 1, 30, and 60, individual stool samples were collected for bacterial counts in the stool, blood samples for blood counts, and serum for biochemical tests. Total bacterial counts in feces were lower in group T on days 30 and 60 of the experiment, while total coliforms and E coli. were lower in this group on day 60. Total leukocyte counts were lower on day 60 in group T, unlike the neutrophil count, higher in group T on day 30, and eosinophils on day 60. However, the lymphocyte count was lower in group T on days 30 and 60. There was an increase in globulin and total protein in group T on day 60. We conclude that the tested homeopathic causes neutrophils and eosinophils' stimulation and increases globulins levels even with reduced lymphocytes. The daily consumption of homeopathic by dogs decreases the intestinal bacterial load, resulting in less environmental contamination and animal and human colibacillosis risks.